Effectiveness and Durability of a Workplace Sedentary Behavior Intervention Based on the Total Worker Health® Approach - Brad Wipfli; Sara Wild; Ginger Hanson; Steven A. Shea; Kerri Winters-Stone; Wura Olawole; Renee Kozlowski; Saurabh S. Thosar (Behavioral Sciences)
We used the Total Worker Health® approach to develop a multi-component workplace sedentary behavior intervention and tested intervention effectiveness in a cluster randomized trial. Participants (n = 198; 75% female) were recruited from three call-centers (two intervention and one usual practice control). All worksites received pedal stand active workstations. The usual practice site received no additional support, while the intervention group completed a six-month program of activities including computer-based training, behavioral self-monitoring, health and safety discussions, and pedaling competitions. Data collection included a survey, a physical health assessment, and accelerometer measures of sedentary behavior, physical activity, and sitting/standing time. Primary analyses were generalized estimating equations comparing changes between intervention and usual practice conditions over time, along with analyses of changes in both groups combined over time. Six-month results revealed less prolonged sitting and reductions in musculoskeletal pain in both groups (all p < 0.05), while the intervention group showed additional improvements in moderate physical activity (p < 0.001) and use of pedal stands (p < 0.01). At 12-months, the additional physical activity and pedal stand use in the intervention group regressed to baseline levels, while reductions in prolonged sitting in both groups were durable (p < 0.01). This study adds to previous research showing the effectiveness of the Total Worker Health® approach for workplace health and safety. Results also show that, while providing employees with health and safety resources is beneficial, providing ongoing support for the adoption and use of resources is more effective.